2001
DOI: 10.1094/phyto.2001.91.9.891
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering ofFrankliniella fusca(Thysanoptera: Thripidae) on Winter Annual Weeds Infected withTomato spotted wilt virusand Patterns of Virus Movement Between Susceptible Weed Hosts

Abstract: Overwintering of tobacco thrips, Frankliniella fusca, was investigated on common winter annual host plants infected with Tomato spotted wilt virus (TSWV). Populations of tobacco thrips produced on TSWV-infected plants did not differ from those produced on healthy plants, whereas populations varied greatly among host plant species. The mean per plant populations of F. fusca averaged 401, 162, and 10 thrips per plant on Stellaria media, Scleranthus annuus, and Sonchus asper, respectively, during peak abundance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 24 publications
0
62
0
1
Order By: Relevance
“…Among those, Frankliniella occidentalis (western flower thrips) and Frankliniella fusca (tobacco thrips) are the most efficient vectors in the southeastern United States (26). Unlike the other arthropod-borne members of the Bunyaviridae, old second instar larvae and adults can become transmitters of TSWV only if the virus is acquired by the thrips in the first instar larval stage (27,28).…”
mentioning
confidence: 99%
“…Among those, Frankliniella occidentalis (western flower thrips) and Frankliniella fusca (tobacco thrips) are the most efficient vectors in the southeastern United States (26). Unlike the other arthropod-borne members of the Bunyaviridae, old second instar larvae and adults can become transmitters of TSWV only if the virus is acquired by the thrips in the first instar larval stage (27,28).…”
mentioning
confidence: 99%
“…However, further work is needed to clarify the extent to which weeds are involved in the infection cycle of MYSV, since only a few species of weeds were used in these experiments. In addition, titres and the localities of MYSV in weeds, food consumption and survival rates of T. palmi from MYSV-infected weeds, and growth stage of the host plants are presumed to affect the acquisition and transmission of tospovirus (Groves et al 2001;Okazaki et al 2009). In our study, RT-PCR was used for the detection of MYSV.…”
Section: Discussionmentioning
confidence: 99%
“…Tomato spotted wilt virus (TSWV) of the genus Tospovirus has a broad host range consisting of more than 1,000 species (Parrella et al 2003), including many weed species (Chatzivassiliou et al 2007;Groves et al 2001;McPherson et al 2003;Mertelik et al 1996;Okazaki et al 2007). Weeds not only carry viruses, but also provide habitats for vectors such as thrips during non-cropping periods.…”
mentioning
confidence: 99%
“…However, it seems more likely they transmit TSWV to alternate host plants where it can be acquired by subsequent generations of tobacco thrips in the spring, which then transmit the virus to other plants including peanuts. Groves et al (2001) demonstrated that both tobacco thrips and western flower thrips (F. occidentalis) overwintering on infected winter annual weeds spread TSWV to other weeds in late winter and early spring.…”
Section: Discussionmentioning
confidence: 99%